Thinking Literature across Continents - Ghosh, Ranjan; Miller, J. Hillis (Joseph Hillis), 1928-2021 (Book collections on Project MUSE., 2016)
'Thinking Literature across Continents' finds Ranjan Ghosh and J. Hillis Miller--two thinkers from different continents, cultures, training, and critical perspectives--debating and reflecting upon what literature is and why it matters. Ghosh and Miller do not attempt to formulate a joint theory of literature; rather, they allow their different backgrounds and lively disagreements to stimulate generative dialogue on poetry, world literature, pedagogy, and the ethics of literature. Addressing a varied literary context ranging from Victorian literature, Chinese literary criticism and philosophy, and continental philosophy to Sanskrit poetics and modern European literature, Ghosh offers a transnational theory of literature while Miller emphasizes the need to account for what a text says and how it says it. This book highlights two minds continually discovering new paths of communication and two literary and cultural traditions intersecting in productive and compelling ways.